The Effect of Structured Positive Affirmation on Elementary Students’ Motivation in Physical Education Learning - Andri Setiawan; Tatang Muhtar; Muhammad Nur Alif; Anggi Setia Lengkana (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2026)
This study aimed to examine the effectiveness of positive affirmation interventions in improving elementary school students’ learning motivation. The method used was a quasi-experimental design with a non-equivalent control group design. The study involved 164 fourth-grade elementary school students from 10 schools in the Rancakalong District, consisting of 82 students in the experimental group and 82 students in the control group. The experimental group received positive affirmation interventions before the learning process for 12 meetings, while the control group participated in conventional learning activities. Data were collected using pre-test and post-test questionnaires adapted from the Motivated Strategies for Learning Questionnaire (MSLQ). The results showed that the experimental group experienced an increase in the mean score from 62.83 to 66.39, while the control group increased from 62.89 to 63.26. The Independent Samples T-Test revealed a significant difference between the two groups with a significance value of 0.001 (p < 0.05) and a t-value of 3.433. In addition, the N-Gain analysis indicated that the experimental group achieved a mean N-Gain score of 0.3595 (35.95%), categorized as moderate or fairly effective, whereas the control group obtained an N-Gain score of 0.0108 (1.07%), categorized as low. These findings indicate that the consistent implementation of positive affirmations significantly improved students’ learning motivation and active classroom participation in Physical Education learning. The novelty of this study lies in the implementation of a structured affirmation pattern integrated directly into physical education learning routines to strengthen children’s self-efficacy from an early age.